Aspectos tomográficos da coluna cervical de equinos - Souza, L.P. [UNESP]; Machado, V.M.V. [UNESP]; Santos, R.V. [UNESP]; Evangelista, F.C. [UNESP]; Vulcano, L.C. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2012)
Descreveu-se a anatomia da região cervical de equinos adultos, com base em imagens obtidas no exame de tomografia computadorizada helicoidal realizado em peças anatômicas de equinos adultos. A tomografia computadorizada foi o método de imagem diagnóstica de escolha e possibilita as reconstruções de imagens tridimensionais e em outros planos anatômicos, como sagital e coronal. Todas as imagens foram adquiridas e avaliadas em filtro e janela para tecido ósseo. Observaram-se diferenças anatômicas e as particularidades normais das vértebras, principalmente da região occipitoatlantoaxial, a qual apresenta maior incidência de alterações.

The anatomy of the cervical spine of mature horses based on images obtained with a helical computed tomography examination performed on anatomic specimens was studied. Computed tomography was the diagnostic imaging method of choice and allowed three-dimensional reconstructions of images and other anatomical planes, such as coronal and sagittal. All images were acquired and evaluated in the filter and window to bone tissue. It was possible to demonstrate the anatomical differences and peculiarities of the normal vertebrae, particularly the occipito-atlantoaxial region, which has a higher incidence of changes to assist in the visualization of any change of the bone pattern on CT studies.
Tomographic imaging of the cervical spine of horses
Keywords: cavalo; tomografia computadorizada helicoidal; coluna cervical; horse; helical CT; cervical